Signal Game Analysis on the Effectiveness of Coal Mine Safety Supervision Based on the Affective Events Theory. (26th June 2020) - Yang, Xue; Tian, Yang; Feng, Kai; Yang, Juan; Zhang, Shu-hui; Wang, Shengnan
Abstract : The main cause of coal mine safety accidents is the unsafe behavior of miners who are affected by their emotional state. Therefore, the implementation of effective emotional supervision is important for achieving the sustainable development of coal mining enterprises in China. Assuming rational players, a signaling game between miners (emotion-driven and judgement-driven) and managers is established from the perspective of Affective Events Theory in order to examine the impact of managers' emotions on coal miners' behavior; it analyzes the players' strategy selections as well as the factors influencing the equilibrium states. The results show that the safety risk deposits paid by managers and the costs of emotion-driven miners disguising any negative emotions affect equilibrium. Under the separating equilibrium state, the emotional supervision system faces "the paradox of almost totally safe systems" and will be broken; the emotion-driven miners disguising any negative emotions will be permitted to work in the coal mine, creating a safety risk. Under the pooling equilibrium state, strong economic constraints, such as setting suitable safety risk deposits, may achieve effective emotional supervision of the miners, reducing the safety risk. The results are verified against a case study of the China Pingmei Shenma Group. Therefore, setting a suitable safety risk deposit to improve emotional supervision and creating punitive measures to prevent miners from disguising any negative emotions can reduce the number of coal mine safety accidents in China.